Impact of acute coronary syndrome on clinical outcomes after revascularization with the dual‐therapy CD34 antibody‐covered sirolimus‐eluting Combo stent and the sirolimus‐eluting Orsiro stent. Issue 1 (15th November 2022) - Jakobsen, Lars; Christiansen, Evald H.; Freeman, Phillip; Kahlert, Johnny; Veien, Karsten; Maeng, Michael; Raungaard, Bent; Ellert, Julia; Kristensen, Steen D.; Christensen, Martin K.; Terkelsen, Christian J.; Thim, Troels; et al.
Abstract: Objectives: To compare the efficacy and safety of the dual‐therapy CD34 antibody‐covered sirolimus‐eluting Combo stent (DTS) and the sirolimus‐eluting Orsiro stent (O‐SES) in patients with and without acute coronary syndrome (ACS) included in the SORT OUT X study. Background: The incidence of target lesion failure (TLF) after treatment with modern drug‐eluting stents has been reported to be significantly higher in patients with ACS when compared to patients without ACS. Whether the results from the SORT OUT X study apply to patients with and without ACS remains unknown. Methods: In total, 3146 patients were randomized to stent implantation with DTS ( n  = 1578; ACS: n  = 856) or O‐SES ( n  = 1568; ACS: n  = 854). The primary end point, TLF, was a composite of cardiac death, target‐lesion myocardial infarction (MI), or target lesion revascularization (TLR) within 1 year. Results: At 1 year, the rate of TLF was higher in the DTS group compared to the O‐SES group, both among patients with ACS (6.7% vs. 4.1%; incidence rate ratio: 1.65 [95% confidence interval, CI: 1.08–2.52]) and without ACS (6.0% vs. 3.2%; incidence rate ratio: 1.88 [95% CI: 1.13–3.14]). The differences were mainly explained by higher rates of TLR, whereas rates of cardiac death and target lesion MI did not differ significantly between the two stent groups in patients with or without ACS Conclusion: Compared to the O‐SES, the DTS was associated with a higher risk of TLF at 12 months in patients with and without ACS. The differences were mainly explained by higher rates of TLR.